The Effect Of Cassava Flour Substitution On The Physical Properties And Sensory Quality Of Apang Coe - Shakila Rafa; Cucu Cahyana; Mutiara Dahlia (Yayasan Riset dan Pengembangan Intelektual, 2026)
Apang Coe is a traditional steamed cake from Manado, North Sulawesi, whose characteristic expansion and surface cracks depend on the behavior of its flour matrix. This study evaluated the effects of substituting cassava flour for 20%, 30%, and 40% of the total flour premix on physical properties and sensory quality. The experiment was conducted at the Pastry and Bakery Laboratory at Universitas Negeri Jakarta from August 2025 to July 2026. Expansion and relative cracking were measured in triplicate and analyzed by one-way analysis of variance; Duncan's test was used to follow up on significant results. Sensory quality was assessed by 45 semi-trained panelists (15 independent panelists per treatment) using eight five-point attribute scales, and the data were analyzed as individual scores with a tie-corrected Kruskal–Wallis test. Mean expansion increased from 89.93% at 20% substitution to 101.67% at 30% and 119.73% at 40%. The effect was significant (F(2,6)=6.07; p=0.036); the 40% treatment differed from the 20% treatment, with the 30% treatment intermediate. Relative cracking did not differ (p=0.770). None of the sensory attributes—surface cracking, color, brown-sugar aroma, cassava aroma, softness, pore structure, sweetness, or cassava taste—differed significantly (p=0.197–0.757). The 20% formulation is proposed as a practical, balanced formula because it retains the characteristic color, aroma, and pores, and a low cassava note. However, it was not statistically superior in overall sensory quality.